Perspectives on Cognitive Phenotypes and Models of Vascular Disease. Issue 7 (5th May 2022) - Muratoglu, Selen C.; Charette, Marc F.; Galis, Zorina S.; Greenstein, Adam S.; Daugherty, Alan; Joutel, Anne; Kozel, Beth A.; Wilcock, Donna M.; Collins, Emily C.; Sorond, Farzaneh A.; Howell, Gareth R.; Hyacinth, Hyacinth I.; et al.
Abstract : Clinical investigations have established that vascular-associated medical conditions are significant risk factors for various kinds of dementia. And yet, we are unable to associate certain types of vascular deficiencies with specific cognitive impairments. The reasons for this are many, not the least of which are that most vascular disorders are multi-factorial and the development of vascular dementia in humans is often a multi-year or multi-decade progression. To better study vascular disease and its underlying causes, the National Heart, Lung, and Blood Institute of the National Institutes of Health has invested considerable resources in the development of animal models that recapitulate various aspects of human vascular disease. Many of these models, mainly in the mouse, are based on genetic mutations, frequently using single-gene mutations to examine the role of specific proteins in vascular function. These models could serve as useful tools for understanding the association of specific vascular signaling pathways with specific neurological and cognitive impairments related to dementia. To advance the state of the vascular dementia field and improve the information sharing between the vascular biology and neurobehavioral research communities, National Heart, Lung, and Blood Institute convened a workshop to bring in scientists from these knowledge domains to discuss the potential utility of establishing a comprehensive phenotypic cognitive assessment of a selected set of existing mouse models, representative of the spectrum of vascular disorders, with particular attention focused on age, sex, and rigor and reproducibility. The workshop highlighted the potential of associating well-characterized vascular disease models, with validated cognitive outcomes, that can be used to link specific vascular signaling pathways with specific cognitive and neurobehavioral deficits.